ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI TINGKAT TURNOVER PADA PEKERJA GENERASI Z DAN GENERASI MILENIAL DI KOTA BLITAR - Dwi Danesty Deccasari; Viona Anjelina Ade Erika; Marli Marli (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2025)
This study aims to identify the factors causing turnover among Generation Z and Millennials in Blitar City. The research uses a quantitative approach analyzed through factor analysis, with the subjects being Generation Z and Millennial workers. Data were collected using questionnaires distributed via Google Forms on social media, with a sample of 78 respondents. The data were analyzed descriptively and through path analysis using the Smart-PLS program. The results indicate that five factors contribute to turnover among Generation Z and Millennials: Work Life, Job Satisfaction, Incentives & Rewarding, Job Stress, and Workload. The findings show that Job Satisfaction and Workload factors influence turnover. It is hoped that companies in Blitar City will pay attention to employees' Job Satisfaction and Workload to minimize employee turnover.